2006
DOI: 10.1586/14760584.5.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Are tick-borne encephalitis vaccines interchangeable?

Abstract: Two tick-borne encephalitis vaccines produced by two vaccine manufacturers are available in most European countries. A question that is frequently asked regarding these two vaccines concerns their exchangeability, however, to date, no detailed assessment has been published. This review analyzes clinical studies investigating these two vaccines and describes possible approaches to boost or continue uncompleted primary immunization schedules, with either of the two tick-borne encephalitis vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 7 publications
0
12
0
3
Order By: Relevance
“…62 , 63 Recent clinical data show that they may also be conditionally interchangeable during primary vaccination with conventional schedules. 64 However, data are still lacking and thus, a change of vaccines is only acceptable after careful consideration and then only in specific cases, e.g., vaccine shortage. 65 …”
Section: Discussionmentioning
confidence: 99%
“…62 , 63 Recent clinical data show that they may also be conditionally interchangeable during primary vaccination with conventional schedules. 64 However, data are still lacking and thus, a change of vaccines is only acceptable after careful consideration and then only in specific cases, e.g., vaccine shortage. 65 …”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from clinical studies have demonstrated that the replacement of one TBE vaccine by the other as a booster vaccination (after complete primary immunization) is certainly possible. 10 However, differences in the vaccines' antigen amount, excipients and production process put the viability of this option into question. In particular, it has been hypothesized that a potentially inadequate immune response could be expected when the vaccine brand is changed during the course of primary vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the common conclusion from all these studies is that despite being considered analogous vaccines, the immune responses to Encepur ® Children and FSME-IMMUN ® Junior are not identical. Several explanations for this observation have been suggested before [9,18] and include intrinsic differences in the vaccine formulations such as in the antigenic content and/or the excipients added. Ultimately, regardless of their relative differences in immune response, it is well established that both Encepur ® and FSME-IMMUN ® elicit effective immune responses against TBE after a complete primary vaccination series in adults and children [9,11,17,19,20], even if used interchangeably [9,18].…”
Section: Discussionmentioning
confidence: 99%